OTONOMI DAERAH DI NEGARA KESATUAN REPUBLIK INDONESIA - M. Agus Santoso (Sekolah Tinggi Ilmu Administrasi Lembaga Administrasi Negara, 2009)
In the United Nation of Republic of Indonesia the highest authorization holder is center government, but geographics of Republic of Indonesia is very large and divided into islands and archipelegoes and large and small regions so in running authorization, center government obliges to give part of its authority to regions, in order to manage each region. It is called decentralization or Region Authonomy. The principle of Republic of Indonesia can not be separated with principle of Region Authonomy, it includes in section I verse I Undang Undang Dasar 1945 and its and section 18 amandement, therefore Region Authonomy is sub system of Republic of Indonesia Authorization system. If it looked from Organization of Region Authonomy in Indonesia has organized since Freedom of Indonesia, and it happened before Indonesia Freedom, Holland and Japan have done Region Authonomy version Colonial, so it is impossible if Region Authonomy in Indonesia must be maintained and develops up to now.